ANALISIS FORMING LIMIT DIAGRAM (FLD) PADA MATERIAL TEMBAGA - Mansyur Abdul Shaleh; Atik Setyani (Journal of Metallurgical Engineering and Processing Technology, 2022)
Forming Limit Diagram also known as forming limit curve, is used in sheet metal forming to predict sheet metal forming behavior. The diagram contains a graphical description of a material failure test, such as the hollow dome test. This study aims to make a Forming Limit Diagram (FLD) of copper material with a thickness of 0.5 mm through the Nakazima standard FLD test using the experimental method research process. FLD test results are strengthened by tensile testing using the ASTM E8 standard with a cutting angle at 00 450, and 900 against the plate rolling direction. The results of the FLD test analysis on copper with a thickness of 0.5 mm show that the specimen has a maximum major strain value of 17.96% and a maximum minor strain of 7.05% while for tensile strength a cutting angle of 450 has the greatest maximum stress of 124,414 MPa, and experienced the greatest strain of 28.8%. specimen 00 true stress was 85.934 MPa, true strain was 14.5 %, and specimen 900 was true stress was 116.138 MPa, true strain was 25.4 %.